Applicable Law for Construction Contracts under FIDIC General Conditions – the Role of Chosen Law - Jovanović, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
In academic literature on construction contracts governed by the FIDIC General Conditions, extensive attention has been given to dispute resolution, particularly the various mechanisms established within these conditions. Nevertheless, the question of the applicable law governing the substantive aspects of disputes remains largely underexplored. The FIDIC General Conditions allow parties to select the law of a specific state or jurisdiction to govern their contractual relationship. This choice of law plays a crucial role in shaping the interpretation and application of FIDIC contracts. While FIDIC contracts are meticulously designed to provide a comprehensive legal and technical framework for international construction projects, they do not operate in a legal vacuum. Instead, they are subject to the constraints and requirements of the selected national law. This paper examines how the applicable law influences key aspects of FIDIC contracts, particularly by enforcing mandatory legal norms that override the default provisions of the FIDIC General Conditions and by shaping the interpretation of legal concepts and abstract contractual terms within these standard conditions. Furthermore, the paper explores whether the UNIDROIT Principles of International Commercial Contracts can be chosen as the governing legal framework for FIDIC contracts and assesses their role in international construction disputes. The analysis underscores that the selection of applicable law is far more than a formality, it is a fundamental factor in the functioning of the FIDIC contractual system, with profound implications for dispute resolution, contract enforcement and legal certainty throughout the lifecycle of international construction projects.